"Jag känner mig lite manlig när jag bryter mot de manliga normerna": Om maskulinitet, skönhet och gränsdragande överskridande - Egeberg Holmgren, Linn (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
This article is about cosmetics, masculinity and the esthetisation of the male body as an arena of meaning in relation to gender. Experiments with the appearance are challenging the border between femininity and masculinity, while at the same time new limiting borders are created. To be "unmanly" is talked about by the interviewed men as a new form of being manly. Cosmetics can show, apart from beautifying, that you are fashion conscious, equal to women and no homophobe. The growing care about appearance among men and the increased exposure of the male body is often called a feminisation. Here is argued that rather than being a feminisation in the form of an objectification, it should be understood as a successful project of masculinity, one of the expressions of hegemonic masculinity.